2022
DOI: 10.1002/er.8415
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and viscosity of Al 2 O 3 ‐ZnO‐MWCNT‐EG ternary nanofluid

Abstract: Summary Hybrid nanofluids exhibit enhanced thermal properties compared to their base fluid which makes them more suitable as heat transfer fluids for various applications including solar thermal energy conversion. In the present study, ethylene glycol‐based ternary nanofluid composed of Al2O3, ZnO and multiwall carbon nanotube nanoparticles is synthesized and analyzed for its thermophysical properties such as viscosity and thermal conductivity for different volume concentrations. Thermal conductivity was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…There is a non-linear positive correlation between temperature and thermal conductivity, and the strengthening trend gradually weakens. Mohanan et al [136] measured the thermal conductivity of Al 2 O 3 -EG by the transient hot wire method at a temperature of 25 • C and 40 • C, and the experimental results obtained are consistent with the above conclusions. Suganthi et al [137] studied the variation in the thermal conductivity of ZnO nanofluids with temperature under high-temperature conditions, and the results showed that the thermal conductivity decreased with increasing temperature.…”
Section: Influencing Factorssupporting
confidence: 56%
See 1 more Smart Citation
“…There is a non-linear positive correlation between temperature and thermal conductivity, and the strengthening trend gradually weakens. Mohanan et al [136] measured the thermal conductivity of Al 2 O 3 -EG by the transient hot wire method at a temperature of 25 • C and 40 • C, and the experimental results obtained are consistent with the above conclusions. Suganthi et al [137] studied the variation in the thermal conductivity of ZnO nanofluids with temperature under high-temperature conditions, and the results showed that the thermal conductivity decreased with increasing temperature.…”
Section: Influencing Factorssupporting
confidence: 56%
“…Similarly, lyahraja et al [157] observed a comparable outcome when investigating Ag nanofluids, revealing a non-linear negative correlation between temperature and viscosity. Bindu et al [136] examined viscosity changes in a ternary nanofluid composed of "Al 2 O 3 -ZnO-MWCNT-EG". The experimental data indicated that the viscosity index at 70 • C was only approximately half of that at 40 • C, highlighting a substantial downward trend.…”
Section: The Viscosity Prediction Modelmentioning
confidence: 99%
“…[39]. In a study by Bindu et al, comparing different nanofluids [40], it was found that using carbon nanotubes (CNT) nanofluid with low viscosity resulted in higher system efficiency compared to using base fluid or Ag-MgO nanofluid with higher viscosity. Therefore, low viscosity nanofluids are preferable for photovoltaic thermal systems as they enhance system efficiency and reduce pressure drop.…”
Section: Viscositymentioning
confidence: 99%
“…The need for enhanced thermal conductivity and heat transmission has driven the development of ternary hybrid nanofluids, known as stable mixtures of three distinct varieties of nanoparticles in a base fluid, offering enhanced properties compared to single and hybrid nanofluids. This new extended nanofluid can help optimize heat transmission in various engineering and industrial settings [21]. Ramadhan et al [22] dispersed Al 2 O 3 (alumina), TiO 2 (titania), and SiO 2 (silica) in ethylene glycol to create a ternary hybrid nanofluid.…”
Section: Introductionmentioning
confidence: 99%